Cold victory : a novel - Marlantes, Karl (Atlantic Monthly Press, 2024)
"Helsinki, 1947. Finland teeters between the Soviet Union and the West. Everyone is being watched. A wrong look or a wrong word could end in catastrophe. Natalya Bobrova, from Russia, and Louise Koski, from the United States, are young wives of their country's military attachés. When they meet at an embassy party, their husbands, Arnie and Mikhail, both world-class skiers, drunkenly challenge each other to a friendly-but secret-cross-country wilderness race. Louise is delighted, but Natalya is worried. Stalin and Beria's secret police rule with unforgiving brutality. If news of the race gets out and Mikhail loses, Natalya knows it would mean his death, her imprisonment, and the loss of her two children. Meanwhile, Louise, who is childless, uses the race as an opportunity to raise money for a local orphanage, naive to the danger it will bring to Natalya and her family. Too late to stop Louise's scheme, a horrified Natalya watches as news of the race spreads across the globe as newspapers and politicians spin it as a symbolic battle: freedom versus communism. Desperate to undo her mistake, Louise must reach Arnie to tell him to throw the race and save Mikhail-but how? The two racers are in a world of their own, unreachable in Finland's arctic wilderness."--